Acute Pancreatitis After Percutaneous Metallic Stent Insertion for Malignant Biliary Obstruction: A Retrospective 2-Center Study - Xu, Chen; Xu, Guo-xiong; Liu, Sheng; Shi, Hai-bin; Zhou, Wei-zhong (Turkish Journal of Gastroenterology, 2023)
Background/Aims: The current study investigated the incidence, risk factors, and outcomes of acute pancreatitis after percutaneous transhepatic biliary stenting for malignant biliary obstruction. Materials and Methods: From March 2016 to May 2020, a total of 425 patients who underwent percutaneous transhepatic biliary stent- ing for malignant biliary obstruction were included in this 2-center study. After the procedure, we analyzed the incidence, risk factors, and outcomes of acute pancreatitis. Results: On follow-up, 79 (18.6%) patients showed increased serum amylase levels, of whom 41 (9.6%) developed pancreatitis. On binary logistic regression analysis, stent across the duodenal papilla (odds ratio = 8.54; 95% CI = 3.54-20.62; P < .001) and visualization of the pancreatic duct (odds ratio = 9.87; 95% CI = 4.67-20.86; P < .001) were significant risk factors of pancreatitis after the procedure. Using conservative therapy, all patients were successfully managed at a mean of 3.5 days (range 1-6 days), and no severe pancreatitis happened. Conclusion: Acute pancreatitis is a relatively common complication after percutaneous transhepatic biliary stenting. Stent across the duodenal papilla and visualization of the pancreatic duct are independent risk factors.